Lecturer-student interaction in English-medium science lectures: an investigation of perceptions and practice at a Sri Lankan university where English is a second language - Abdul Majeed, Mohamed Navaz (2012)
This study arises from two contextualised problems faced by the students at the Faculty of Applied Sciences (FAS) of a small university in Sri Lanka. These problems are: students’ lecture comprehension difficulties and limited oral language proficiency in their second language (i.e. English). The ideas developed in this study are based on the argument that dialogic lecturer-student interaction, which enables students to take a more active role in discussions compared to the use of recitation scripts (questions-answers-evaluations) developed in non-dialogic interactions, is likely to be beneficial for students’ content and language development. Although there have been studies at primary level, there has so far been little research into dialogic interaction in tertiary-level L1 Science classes, and none yet carried out in the L2 context. Therefore, this study investigates the extent of dialogic interaction practised at FAS, in conjunction with a thorough consideration of the factors that influence interaction between lecturers and students. This study, involving 30 students and 4 lecturers, was undertaken as a pioneer study in this context in Asia by analysing L2 lectures given at FAS. Data were collected from lecturer and student questionnaires, lecturer interviews, student group interviews, observations of 24 lectures and audio recordings. Of the observed lectures, a total of 12 from Biotechnology, Animal Physiology, Physics and Statistics were transcribed verbatim and analysed using an analytical framework, which was especially designed to analyse the FAS lecture discourse. This framework was also used to locate these lectures on a scale from monologic to dialogic. The study revealed the complexity of the perception-practice dynamic, and the multi-faceted sub-set of factors which influenced students' and lecturers’ behaviour in class, and their perception of that behaviour. Students’ lecture comprehension problems and classroom interaction were influenced by their language proficiency, though the students considered the lecturers’ lecture delivery style to be more important than their own language proficiency. In this study it was revealed that a culturally embedded behaviour perpetuated by senior students, known as ragging (a kind of bullying), restricted the classroom interaction of the students. In terms of lecture delivery style, of all the observed lectures only two contained some interactional episodes in addition to monologic segments, while the others were found to be highly or mostly monologic. Students were also found not to be cooperating with lecturers in classroom interaction, despite stating a preference for learning through interaction. The students asked only very few questions in all the observed lectures, and answered in a limited number of lectures. The lecturers asked more knowledge testing questions than any other kind, while there were only a few concept development questions – the type which can help develop dialogic interaction. Overall, this investigation, which demonstrates the importance of combining studies of perception with detailed analysis of the discourse itself, indicates limited lecturer-student interaction as well as a clear lack of dialogic interaction in English-medium Science lectures at this particular university. In addition, it is argued that the innovative analytical framework designed to analyse the lectures delivered in the English Medium Instruction (EMI) context of the present study can be useful for other lectures which are commonly delivered as monologic in both L1 and L2 contexts. Finally, it also stresses the importance of investigating the influence of cultural and behavioural factors, such as ragging, on classroom learning.